Pengaruh Kualitas Pelayanan dan Lokasi Terhadap Keputusan Pembelian Konsumen pada Restoran Jepang Ale's Place Cipoho Sukabumi - Mintawati, Hesri; Desianti, Lisa Chandrasari; Sonia, Citra; Abdurrahman, Abdan; Iqbal, M. (Neolectura, 2024)
This study examines the influence of service quality and location on consumer purchasing decisions at Ale's Place Japanese restaurant, Cipoho, Sukabumi. Service quality, which includes service speed, staff friendliness, and cleanliness, as well as the restaurant's strategic location, are important factors that can influence customer satisfaction and loyalty. This study used qualitative methods with data collected using observation, interview, and documentation techniques to consumers who have made at least one purchase in the last six months. The results of the study show that good service quality can significantly increase customer satisfaction and encourage repeat purchases. Although the location of the restaurant is not entirely strategic, the uniqueness of the concept and quality of service still attract customers. Therefore, Ale's Place should focus on improving service quality and consider additional factors such as price and promotion to retain and attract more customers.